Evaluation of drought using satellite solar-induced chlorophyll fluorescence during crop development stage over Xinjiang, China. (January 2022) - Pandiyan, Sanjeevi; Navaneethan, C.; Vijayan, R.; Gunasekaran, G.; Khan, K.Y.; Guo, Ya
Highlights: Drought analysis with spatial–temporal variations was performed. SIF contains information on SM, PPT, SPEI, and ET. SPEI and ET have higher sensitivity in response to drought than SM and PPT. Abstract: The effectiveness of satellite solar-induced chlorophyll fluorescence (SIF) for drought evaluation was measured in this study. Here we compare the association of SIF with soil moisture (SM), precipitation (PPT), standardized precipitation evapotranspiration index (SPEI), and ratio of evapotranspiration (ET) to monitor the drought stress on crop growth. A severe drought occurrence was observed in 2015 as compared to other years between 2007 and 2017 in Xinjiang of China. In the period of this drought, the changes of SIF and SIF normalized by absorbed photosynthetically active radiation ( Φ F ) were obstinate. SPEI and ET were observed with higher sensitivity and much more constant decline in response to drought than SM and PPT. Moreover, Φ F is highly sensitive to drought than SIF, SIF normalized by photosynthetically active radiation ( SI F PAR ), enhanced vegetation index (EVI), and normalized difference vegetation index (NDVI). The results demonstrate that satellite SIF provides deep insight for drought detection.